Engaging Nursery Rhymes as Literary Works for Teaching English in EFL Students - Eka Anggia Rini (Universitas Muhammadiyah Kotabumi, 2017)
This study aimed to review five articles in engaging nursery rhymes toward teaching literary works in EFL students. By doing library research, the researcher found some problems and the solutions in engaging the nursery rhymes for EFL students. Young learner or children mostly became the subject of nursery rhymes study. Later, Najat and Bradley (2014) concluded that nursery rhymes can be applied for adult learners.